Tackling Corruption Through : Tax Administration Reform - Rahman, Aminur (World Bank, Washington, DC, 2012)
A weak tax administration encourages corruption that benefits both government officials and businesses at the expense of overall tax revenue. Collusive corruption is at the heart of most, if not all, problems related to tax administration. This note examines the drivers of corruption and suggests good-practice measures for reforming tax administration. It is one in a series addressing issues that governments of developing countries face in reforming their tax systems.